Sampah Dan Masyarakat Perkotaan Studi Tentang Pengelolaan Sampah di Kecamatan Tampan Kota Pekanbaru Provinsi Riau - Mardatillah Mardatillah; Yusmar Yusuf; Yohanes Firzal (Pelantar Press, 2023)
Waste when used properly or appropriately, it can have a good or positive impact, even provide economic benefits for every individual and society. Knowledge in waste management is to know the accumulation or collection, transfer or also transportation, and or proper processing and separation of waste. Knowledge of sorting household waste is to know the sorting of waste in accordance with its type in order to provide economic ecological value in the family such as material gains, handicraft objects in the form of bags, wallets, tissue boxes and others made from waste. This study is titled Waste and Urban Communities Study on Waste Management in The Handsome District of Pekanbaru City, Riau Provinces. The results of this study showed and explained that with Waste Bank in the community has a good impact such as increasing understanding of waste management, sorting household waste and even the perceived advantage is that the community has an economic advantage by saving waste and can have handicrafts from waste materials for sale or use alone and can also utilize waste from food waste to become compost crops. However, not all citizens participate or participate and are also less active in this Waste Bank activity programm.